Resin composition, production method, and molded article thereof

A resin composition with specific thermoplastic resin and α-olefin (co)polymer properties addresses moldability issues in extrusion molding, enhancing mechanical properties and stability by preventing slippage and bleed-out, thus improving the quality of molded products.

JP7603367B2Active Publication Date: 2024-12-20MITSUI CHEMICALS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2018208016
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-11-05
Publication Date
2024-12-20
Estimated Expiration
2038-11-05

AI Technical Summary

Technical Problem

Conventional thermoplastic resins used in extrusion molding face issues of poor moldability due to slippage in the extruder, leading to instability in extrusion rate and limitations on extrusion speed, while improving moldability often results in deterioration of mechanical properties in the molded products.

Method used

A resin composition comprising 25 to 99.99% of a thermoplastic resin with specific properties and 0.01 to 3.8% of an α-olefin (co)polymer with defined methyl group index, melting point, molecular weight, and density, which is produced by melt-kneading and masterbatching to prevent slippage and maintain mechanical properties.

Benefits of technology

The resin composition achieves improved moldability without extruder slippage and enhances the mechanical properties of the molded products, ensuring stable extrusion rates and reduced bleed-out, while maintaining excellent mechanical strength and appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603367000001
    Figure 0007603367000001
  • Figure 0007603367000002
    Figure 0007603367000002
Patent Text Reader

Abstract

SOLUTION: There is provided a resin composition containing a thermoplastic resin (A) of 25 to 99.99 mass%, and an α-olefin (co)polymer (B) satisfying following requirements (b-1) to (b-4) of 0.01 to 3.8 mass%. (b-1) A methyl group index measured byH-NMR is 25 to 60%, wherein the methyl group index means percentage of integral value of a peak in a range of 0.50 to 1.15 ppm to integral value of a peak in a range of 0.50 to 2.20 ppm when the α-olefin (co)polymer is dissolved in heavy chloroform,H-NMR is measured, and a solvent peak appeared at 7.24 ppm based on CHClin the heavy chloroform is used as a reference. (b-2) No melting point is observed in a differential scanning calorimetric analysis (DSC). (b-3) weigh average molecular weight (Mw) calculated by a gel permeation chromatography (GPC) is 1,000 to 20,000. (b-4) density measured by a pycnometer method is 810 to 870 kg / m.EFFECT: According to the invention, there can be provided a resin composition improving moldability without causing moldability reduction by slip occurrence in an extruder, and having no deterioration of mechanical physical properties during extrusion molding of a thermoplastic resin, a manufacturing method therefor, and a molded body obtained by the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition that exhibits good moldability during extrusion molding, a method for producing the same, and a molded article obtained by the molding method. [Background technology]

[0002] Thermoplastic resins have been used for various applications as films, sheets, fibers, and other molded products by extrusion molding. In order to obtain molded products with good mechanical properties by extrusion molding, it is common to use resins with low MFR. However, resins with low MFR cause many problems in moldability, such as poor screw engagement, poor melting of the resin, unstable discharge rate due to high extrusion torque, and limited extrusion speed. In addition, the above problems occur depending on the physical properties and shape variations of the resin, the specifications of the extruder, etc., so in recent years, there has been an even stronger demand for improved moldability in order to solve such problems.

[0003] A method of adding a molding aid to a resin and molding it is known as a general method for improving moldability during extrusion molding, etc. For example, a method of applying a molding aid such as oil or polyethylene wax to a thermoplastic resin to be molded and molding it has been studied (for example, Patent Documents 1 and 2).

[0004] However, even if a resin such as polypropylene is extruded using a conventional molding aid, the moldability itself tends to improve, but the mechanical properties of the resulting molded product usually decrease. Therefore, even if a molded product obtained by extrusion molding using a conventional molding aid is used as a molded product such as a film, sheet, or fiber, problems may arise depending on the application.

[0005] Furthermore, when conventional molding aids are added by feeding them into an extruder from a hopper together with a thermoplastic resin, slippage occurs due to the molding aid in the extruder, which inhibits melting of the thermoplastic resin and, conversely, may result in a decrease in moldability. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 5-80492 [Patent Document 2] Special Publication No. 2003-528948 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a resin composition which has excellent moldability without causing a decrease in moldability due to slippage within an extruder during extrusion molding, and which does not impair the mechanical properties of molded articles obtained by extrusion molding, a method for producing the same, and molded articles obtained from the resin composition. [Means for solving the problem]

[0008] The present invention relates to the following items [1] to [6]. [1] A resin composition containing 25 to 99.99 mass% of a thermoplastic resin (A) having a polystyrene-equivalent weight average molecular weight (Mw) of 5,000 or more as measured by gel permeation chromatography (GPC), and 0.01 to 3.8 mass% of an α-olefin (co)polymer (B) satisfying the following requirements (b-1) to (b-4): (b-1) 1 The methyl group index measured by H-NMR is 25 to 60%. (Here, the methyl group index is the index obtained by dissolving the α-olefin (co)polymer in deuterated chloroform.) 1 It is the ratio of the integral value of the peak within the range of 0.50 to 1.15 ppm to the integral value of the peak within the range of 0.50 to 2.20 ppm when H-NMR is measured and the solvent peak appearing at 7.24 ppm based on CHCl3 in deuterated chloroform is used as a reference. (b-2) No melting point is observed in differential scanning calorimetry (DSC). (b-3) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 20,000. (b-4) Density measured by pycnometer method is 810-870kg / m 3 It is. [2] The resin composition according to [1], wherein the thermoplastic resin (A) is a polyolefin. [3] The resin composition according to [1] or [2], wherein the thermoplastic resin (A) is polypropylene. [4] The resin composition according to any one of [1] to [3], wherein the proportion of components having a molecular weight of less than 5,000 as determined by gel permeation chromatography (GPC) is in the range of 0.7 to 4.5 mass % of all components. [5] A method for producing the resin composition according to any one of [1] to [4], comprising the steps of kneading 0.1 to 100 parts by mass of the α-olefin (co)polymer (B) with 100 parts by mass of the thermoplastic resin (A) to obtain a masterbatch, and kneading the thermoplastic resin (A) with the masterbatch in an extruder. [6] A molded article comprising the resin composition according to any one of [1] to [4]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a resin composition which has excellent moldability without causing a decrease in moldability due to slippage in an extruder during extrusion molding of a thermoplastic resin, and further, does not impair the mechanical properties of the molded article obtained by extrusion molding; a method for producing the same; and a molded article obtained from the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. In the following description, the numerical range "N 1 More than N 2 Below” (N 1 and N 2 indicate the lower and upper limits of the numerical range, respectively), simply expressed as "N 1 ~N 2For example, an α-olefin having 3 to 20 carbon atoms is sometimes described as an “α-olefin having 3 to 20 carbon atoms.”

[0011] The resin composition according to the present invention contains 25 to 99.99 mass % of a thermoplastic resin (A) having specific physical properties, and 0.01 to 3.8 mass % of an α-olefin (co)polymer (B) having specific physical properties.

[0012] Thermoplastic resin (A) The thermoplastic resin (A) used in the present invention is a thermoplastic polymer having a weight average molecular weight (Mw) of 5,000 or more in terms of polystyrene measured by gel permeation chromatography (GPC), or a blend thereof.

[0013] The thermoplastic resin (A) used in the present invention is not particularly limited, and examples thereof include polyolefins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, polybutene, cyclic olefin polymers, ethylene-propylene copolymers, and cyclic olefin copolymers; styrene-based polymers and hydrogenated products thereof such as polystyrene, acrylonitrile-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, styrene-butadiene copolymers, and styrene-isoprene copolymers; polyvinyl chloride, polyvinylidene chloride; vinyl carboxylic acid polymers and vinyl carboxylic acid ester polymers such as polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polymethyl methacrylate, and polyethyl methacrylate; ethylene-methacrylic acid copolymers, ethylene-methacrylic acid ester copolymers, ethylene-vinyl acetate copolymers, and ethylene-vinyl alcohol copolymers; polycarbonates, polymethacrylates; polyesters such as polyethylene terephthalate and polybutylene terephthalate; nylon 6, nylon 11, nylon 12, nylon 46, nylon 66, and nylon M Examples of the resin include polyamides such as XD6, fully aromatic polyamides, and semi-aromatic polyamides; polyacetals, and blends of these resins.

[0014] Among these thermoplastic resins, polyolefins are preferred, with low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene and ethylene-propylene copolymers being more preferred, and polypropylene being particularly preferred.

[0015] When the thermoplastic resin (A) is the above-mentioned polyolefin, the compatibility between the thermoplastic resin (A) and the α-olefin (co)polymer (B) described later is particularly excellent, and a good resin composition can be obtained without deterioration of mechanical properties or bleeding out to the surface.

[0016] The MFR (JIS K 7210; 230° C., test load 2.16 kgf) of the polypropylene is preferably in the range of 0.1 to 60 g / 10 min, more preferably in the range of 0.3 to 20 g / 10 min, and particularly preferably in the range of 0.3 to 10 g / 10 min. When the MFR of the polypropylene is within the above range, a molded article having excellent mechanical properties, heat resistance, chemical resistance, etc. can be obtained.

[0017] <Thermoplastic resin (A) content> The content of the thermoplastic resin (A) in the entire resin composition of the present invention is 25 to 99.99 mass%, preferably 90 to 99.99 mass%, more preferably 96.2 to 99.8 mass%, particularly preferably 97 to 99.4 mass%, and more preferably 98 to 99.4 mass%.

[0018] If the content of the thermoplastic resin (A) in the entire resin composition is less than the lower limit, the properties of the thermoplastic resin (A) may be impaired, and a molded product having excellent mechanical properties, heat resistance, chemical resistance, etc. may not be obtained. On the other hand, if the content of the thermoplastic resin (A) in the entire resin composition exceeds the upper limit, problems such as poor moldability, unstable discharge amount, and limited extrusion speed may occur.

[0019] α-Olefin (co)polymer (B) The α-olefin (co)polymer (B) used in the present invention satisfies the requirements (b-1) to (b-4) described below. In the present invention, the α-olefin (co)polymer is preferably a homopolymer of an α-olefin having 2 to 20 carbon atoms or a copolymer of two or more α-olefins.

[0020] Examples of the α-olefin having 2 to 20 carbon atoms constituting the α-olefin (co)polymer (B) according to the present invention include linear α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tricene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and branched α-olefins such as 3-methyl-1-pentene, 4-methyl-1-pentene, 8-methyl-1-nonene, 7-methyl-1-decene, 6-methyl-1-undecene, and 6,8-dimethyl-1-decene. These α-olefins can be used alone or in combination of two or more.

[0021] Requirements (b-1) 1 The methyl group index measured by H-NMR is 25 to 60% (here, the methyl group index is the methyl group index measured by dissolving the α-olefin (co)polymer (B) in deuterated chloroform). 1 It is the ratio of the integral value of the peak within the range of 0.50 to 1.15 ppm to the integral value of the peak within the range of 0.50 to 2.20 ppm when H-NMR is measured and the solvent peak appearing at 7.24 ppm based on CHCl3 in deuterated chloroform is used as a reference.

[0022] The α-olefin (co)polymer (B) according to the present invention is characterized in that the ratio of methyl groups to the total protons is within a certain range. Generally, the protons of a methyl group are 1It is known that a peak is observed on the high magnetic field side in H-NMR measurement ("Polymer Analysis Handbook" (published by Asakura Publishing, pp. 163-170)). 1 The ratio of the peaks on the high magnetic field side observed when measuring with H-NMR was used as an index of the methyl group. Specifically, α-olefin (co)polymer (B) was dissolved in deuterated chloroform, 1 H-NMR was measured, and the ratio of the integral value of the peak in the range of 0.50 to 1.15 ppm to the integral value of the peak in the range of 0.50 to 2.20 ppm, when the solvent peak due to CHCl3 in deuterated chloroform was used as the reference (7.24 ppm), was used as the methyl group index. Here, the range of 0.50 to 2.20 ppm contains almost all peaks due to α-olefin (co)polymers. Of this range, the peak due to the methyl group is likely to be contained within the range of 0.50 to 1.15 ppm.

[0023] The α-olefin (co)polymer (B) according to the present invention has a methyl group index of 25 to 60%, and a preferred embodiment of the methyl group index is 25 to 40%, and another preferred embodiment of the methyl group index is 40 to 60%. When the methyl group index is within the above range, the compatibility between the α-olefin (co)polymer (B) and the thermoplastic resin (A) is good, and the mechanical properties of the resin composition can be maintained. In particular, when the thermoplastic resin (A) is a polyolefin, the compatibility is excellent due to the similarity of the structure, and in particular, the compatibility between the amorphous part of the polyolefin and the α-olefin (co)polymer (B) is excellent, so that bleeding out can be prevented and the mechanical properties and appearance can be maintained well. This is presumably because the methyl group index is an index indicating the proportion of branches in the α-olefin (co)polymer (B), and when the methyl group index of the α-olefin (co)polymer (B) is within the above range, a certain amount of branches contribute to reducing the intermolecular force of the α-olefin (co)polymer (B), and can be diffused (compatible) well into the amorphous part of the polyolefin.

[0024] The methyl group index in the α-olefin (co)polymer (B) according to the present invention can be controlled by selecting and polymerizing an appropriate α-olefin. For example, homopolymers of α-olefins having 3 to 5 carbon atoms, such as propylene, butene, and isobutene, have too high a ratio of methyl groups to the monomer, making it difficult to adjust the methyl group index within the above range. When attempting to achieve a methyl group index within the above range using a homopolymer, it is necessary to select an α-olefin having 6 to 20 carbon atoms as the α-olefin. A polymer that satisfies such requirements is a higher α-olefin (co)polymer (PAO), which is a preferred embodiment of the α-olefin (co)polymer in the present invention. The details of the higher α-olefin (co)polymer (PAO) will be described later. For example, a homopolymer of ethylene does not have a methyl group, so it is necessary to appropriately copolymerize an α-olefin having 3 to 20 carbon atoms to increase the ratio of methyl groups. A polymer that satisfies such requirements is an ethylene-α-olefin copolymer, which is another preferred embodiment of the α-olefin (co)polymer in the present invention. The details will be described later.

[0025] Requirement (b-2) No melting point was observed in differential scanning calorimetry (DSC). The α-olefin (co)polymer (B) according to the present invention is characterized in that no melting point is observed as measured by differential scanning calorimetry (DSC). Here, "no melting point (Tm) is observed" means that the heat of fusion (ΔH) (unit: J / g) measured by differential scanning calorimetry (DSC) is not substantially measured. "No heat of fusion (ΔH) is substantially measured" means that no peak is observed in the differential scanning calorimetry (DSC) measurement, or the observed heat of fusion is 1 J / g or less.

[0026] The melting point (Tm) and heat of fusion (ΔH) of the α-olefin (co)polymer (B) according to the present invention are determined by analyzing the DSC curve with reference to JIS K7121 when the α-olefin (co)polymer (B) is cooled to -100°C and then heated to 150°C at a heating rate of 10°C / min by differential scanning calorimetry (DSC). If the α-olefin (co)polymer (B) does not have a melting point, it is likely to become liquid at room temperature, and a good flowability improving effect can be obtained. In addition, when the α-olefin (co)polymer (B) is used as a masterbatch obtained by melt-kneading the thermoplastic resin (A) with the above-mentioned thermoplastic resin (A) in advance, the α-olefin (co)polymer (B) is likely to soften and melt the thermoplastic resin (A) contained in the masterbatch, and a good flowability improving effect can be obtained, since the melting point of the α-olefin (co)polymer (B) is not observed.

[0027] Furthermore, when the thermoplastic resin (A) is a polyolefin, if the α-olefin (co)polymer (B) does not have a melting point, the α-olefin (co)polymer (B) will exhibit good compatibility with the amorphous portion of the thermoplastic resin (A) and will not only prevent bleed-out and deterioration of mechanical properties, but will also be expected to exert an effect of imparting good tensile elongation at break to the thermoplastic resin (A) due to the flexibility of the α-olefin (co)polymer (B).

[0028] Requirements (b-3) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 20,000.

[0029] The α-olefin (co)polymer (B) according to the present invention has a weight average molecular weight (Mw) in the range of 1,000 to 20,000, preferably 1,500 to 15,000, more preferably 2,000 to 9,000, and particularly preferably 2,000 to 5,500. If the weight average molecular weight is smaller than the lower limit, the mobility of the α-olefin (co)polymer (B) in the resin composition increases, and bleeding out tends to occur. On the other hand, if the weight average molecular weight of the α-olefin (co)polymer (B) is larger than the upper limit, a sufficient flowability improving effect cannot be obtained, and moldability may not be improved, or compatibility with the thermoplastic resin (A) may be poor, causing a decrease in mechanical properties or bleeding out.

[0030] The molecular weight distribution (Mw / Mn) of the α-olefin (co)polymer (B) according to the present invention, as measured by gel permeation chromatography, is not particularly limited, but is usually 3 or less, preferably 2.5 or less, and more preferably 2 or less. The molecular weight distribution (Mw / Mn) is usually 1.0 or more, and preferably 1.2 or more. If the molecular weight distribution of the α-olefin (co)polymer is broad (Mw / Mn is large), it will contain a large amount of low-molecular-weight or high-molecular-weight components that may cause bleed-out or deterioration of mechanical properties, which is not preferable.

[0031] The weight average molecular weight and molecular weight distribution of the α-olefin (co)polymer (B) according to the present invention can be measured by gel permeation chromatography (GPC) calibrated using a standard substance (monodisperse polystyrene) of known molecular weight.

[0032] Requirements (b-4) Density measured by pycnometer is 810-870kg / m 3 It is. The α-olefin (co)polymer (B) according to the present invention has a density of 810 to 870 kg / m 3 and preferably 820 to 855 kg / m 3 More preferably, it is 830 to 850 kg / m 3and particularly preferably 840 to 850 kg / m 3 When the density of the α-olefin (co)polymer (B) is within the above range, the α-olefin (co)polymer (B) has good compatibility with the thermoplastic resin (A), and the mechanical properties of the resin composition can be maintained. In particular, when the thermoplastic resin (A) is a polyolefin, the amorphous portion of the polyolefin and the α-olefin (co)polymer (B) show excellent compatibility, which prevents bleeding out of the resin composition and maintains good mechanical properties and appearance.

[0033] The difference (Db) between the density of the α-olefin (co)polymer (B) according to the present invention and the density (Da) of the thermoplastic resin (A) (Da-Db) is 10 to 160 kg / m 3 It is preferable that the range is 35 to 140 kg / m 3 More preferably, the range is 40 to 110 kg / m 3 More preferably, the range is 50 to 80 kg / m 3 It is particularly preferable that the range is as follows.

[0034] If the density of the α-olefin (co)polymer (B) is greater than the upper limit of the above range, the α-olefin (co)polymer (B) is poorly compatible with the thermoplastic resin (A), and the mechanical strength of the resin composition may decrease or bleed out, which is not preferable. On the other hand, if the density of the α-olefin (co)polymer (B) is less than the lower limit of the above range, the low flow temperature and high fluidity of the α-olefin (co)polymer (B) do not have a sufficient difference compared to the thermoplastic resin (A), and the α-olefin (co)polymer (B) may not provide a good flow improvement effect, which is not preferable. In other words, if the density of the α-olefin (co)polymer (B) is within the above range, a resin composition having an excellent balance between compatibility and flow improvement effect, a small decrease in mechanical properties, etc., and excellent moldability can be obtained, which is preferable. In particular, when the thermoplastic resin (A) is a polyolefin, it is preferable that the density of the α-olefin (co)polymer (B) is within the above range, since the α-olefin (co)polymer (B) is likely to exhibit good compatibility with the amorphous portion of the thermoplastic resin (A) and bleeding out of the α-olefin (co)polymer (B) and deterioration of the mechanical properties of the resin composition can be suppressed.

[0035] The density of the α-olefin (co)polymer (B) according to the present invention is a value determined by the pycnometer method in accordance with JIS K2249-3, and the density of the thermoplastic resin (A) is a value measured in accordance with the density gradient tube method in JIS K7112.

[0036] <Higher α-olefin (co)polymer> A preferred embodiment of the α-olefin (co)polymer (B) according to the present invention is a (co)polymer of a monomer consisting of one or more α-olefins having 6 to 20 carbon atoms. The (co)polymer of a monomer consisting of one or more α-olefins having 6 to 20 carbon atoms is an α-olefin homopolymer having 6 to 20 carbon atoms, or an α-olefin copolymer having 6 to 20 carbon atoms containing one or more structural units corresponding to an α-olefin having 6 to 20 carbon atoms. In this specification, such an α-olefin (co)polymer may be referred to as a "higher α-olefin (co)polymer" for convenience. Furthermore, such an α-olefin (co)polymer may also contain ethylene and / or an α-olefin having 3 to 5 carbon atoms as a copolymerization component, if necessary, within a range not exceeding 50 mol%. Such a higher α-olefin (co)polymer is generally referred to as PAO.

[0037] In this specification, when an olefin constituting a certain (co)polymer is designated as A, the expression "structural unit derived from A" is sometimes used, which means a "structural unit corresponding to A," that is, a structural unit having a pair of bonds formed by opening the π bond constituting the double bond of A.

[0038] Examples of α-olefins having 6 to 20 carbon atoms used in the production of higher α-olefin (co)polymers (PAO) include linear α-olefins such as 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tricene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and branched α-olefins such as 3-methyl-1-pentene, 4-methyl-1-pentene, 8-methyl-1-nonene, 7-methyl-1-decene, 6-methyl-1-undecene, and 6,8-dimethyl-1-decene. Of these, linear α-olefins having 8 to 12 carbon atoms are preferred, and 1-octene and 1-decene are particularly preferred.

[0039] In the present invention, the content of constituent units derived from a monomer consisting of an α-olefin having 6 to 20 carbon atoms constituting the higher α-olefin (co)polymer (PAO) is in the range of 50 to 100 mol %, preferably 55 to 100 mol %, and more preferably 60 to 100 mol %.

[0040] In the present invention, the content of structural units derived from ethylene constituting the higher α-olefin (co)polymer (PAO) is in the range of 0 to 50 mol %, preferably 0 to 45 mol %, and more preferably 0 to 40 mol %.

[0041] Furthermore, if necessary, the higher α-olefin (co)polymer (PAO) may contain 0 to 30 mol % of a structural unit derived from an α-olefin having 3 to 5 carbon atoms. Examples of such α-olefins having 3 to 5 carbon atoms include linear α-olefins such as propylene, 1-butene, and 1-pentene, and branched α-olefins such as 3-methyl-1-butene. These α-olefins having 3 to 5 carbon atoms may be used alone or in combination of two or more.

[0042] The methyl group index of the higher α-olefin (co)polymer (PAO) is not particularly limited as long as it is within the range of 25 to 60%, but in order to maintain good compatibility with the thermoplastic resin (A), it is preferably 25 to 40%, and more preferably 25 to 35%.

[0043] These α-olefins can be used alone or in combination of two or more. The above-mentioned higher α-olefin (co)polymers (PAO) can be obtained by oligomerization using an acid catalyst such as boron trifluoride or a chromic acid catalyst, as described in U.S. Pat. No. 3,382,291, U.S. Pat. No. 3,763,244, U.S. Pat. No. 5,171,908, U.S. Pat. No. 3,780,128, U.S. Pat. No. 4,032,591, JP-A-1-163136, U.S. Pat. No. 4,967,032, and U.S. Pat. No. 4,926,004. Also, it can be obtained by a method using a catalyst system using a transition metal complex such as zirconium, titanium, hafnium, etc., including a metallocene compound, as described in JP-A-63-037102, JP-A-2005-200447, JP-A-2005-200448, JP-A-2009-503147, and JP-A-2009-501836. As a method for producing higher α-olefin (co)polymers (PAO), oligomerization using an acid catalyst is preferred from the viewpoint of the versatility of the production method and the availability of the resulting α-olefin (co)polymers (PAO). Among the acid catalysts, boron trifluoride is particularly preferred because it can produce a low-order structure.

[0044] Ethylene / α-olefin copolymer Another preferred embodiment of the α-olefin (co)polymer (B) according to the present invention is a copolymer of ethylene and an α-olefin having 3 or more carbon atoms (hereinafter also referred to as "ethylene-α-olefin copolymer"). The α-olefin constituting the ethylene-α-olefin copolymer may be an α-olefin other than ethylene. Typical examples include linear α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and branched α-olefins having 3 to 20 carbon atoms, such as 3-methyl-1-pentene, 4-methyl-1-pentene, 8-methyl-1-nonene, 7-methyl-1-decene, 6-methyl-1-undecene, and 6,8-dimethyl-1-decene. In the ethylene-α-olefin copolymer, these α-olefins may be used alone or in combination of two or more. However, in the present invention, in order to distinguish it from the above-mentioned "higher α-olefin (co)polymer", the content of structural units corresponding to α-olefins having 6 to 20 carbon atoms in the ethylene-α-olefin copolymer is less than 50 mol%. Among these α-olefins, α-olefins having 3 to 10 carbon atoms are preferred, and propylene is particularly preferred, from the viewpoints of the effect of effectively reducing crystallinity to make the resin composition liquid and improving the flowability, and the effect of improving the compatibility between the α-olefin (co)polymer (B) and the thermoplastic resin (A).

[0045] The ethylene-α-olefin copolymer according to the present invention preferably has an ethylene structural unit content of 30 to 80 mol%, more preferably 40 to 75 mol%, even more preferably 40 to 60 mol%, particularly preferably 40 to 55 mol%, and most preferably 40 to 48 mol%. If the ethylene structural unit content is too high or too low, crystallinity may increase, compatibility may deteriorate, and mechanical properties and flowability improving effects may decrease. On the other hand, if the ethylene structural unit content is within the above range, crystallinity is lost, and mechanical properties can be maintained, and good flowability improving effects and improved tensile breaking elongation can be obtained.

[0046] The ethylene content of the ethylene-α-olefin copolymer according to the present invention is 13 It can be measured by C-NMR method, for example, by identifying and quantifying peaks according to the method described below and the method described in "Polymer Analysis Handbook" (published by Asakura Publishing, pp. 163-170).

[0047] The ethylene / α-olefin copolymer according to the present invention has a blockiness (B value) measured by NMR of usually 0.9 or more, preferably 1.0 or more. The B value is a parameter indicating the randomness of the copolymerization monomer sequence distribution, and when the B value is small, the crystallinity is high, and the mechanical properties and flow improvement effect may be reduced.

[0048] The methyl group index of the ethylene-α-olefin copolymer according to the present invention is not particularly limited as long as it is within the range of 20 to 60%, but in order to maintain good compatibility, it is preferably 40 to 60%, more preferably 40 to 55%, and even more preferably 45 to 52%.

[0049] The method for producing an ethylene-α-olefin copolymer is not particularly limited, and examples thereof include a method using a vanadium catalyst consisting of a vanadium compound and an organoaluminum compound, as described in JP-B-2-1163 and JP-B-2-7998. As a method for producing a copolymer with high polymerization activity, a method using a catalyst system consisting of a metallocene compound such as zirconocene and an organoaluminum oxy compound (aluminoxane), as described in JP-A-61-221207, JP-B-7-121969, and Japanese Patent No. 2796376, may also be used, and this method is more preferred since it can reduce the chlorine content of the resulting copolymer and the 2,1-insertion of α-olefin.

[0050] In the method using vanadium catalyst, a larger amount of chlorine compound is used as a cocatalyst than in the method using metallocene catalyst, so there is a high possibility that a small amount of chlorine will remain in the obtained ethylene-α-olefin copolymer (B). On the other hand, in the method using metallocene catalyst, since substantially no chlorine remains, it is preferable in that deterioration of the resin composition due to chlorine can be prevented. The chlorine content is preferably 100 ppm or less, more preferably 50 ppm or less, further preferably 20 ppm or less, and particularly preferably 5 ppm or less. The chlorine content can be quantified by various known methods. For example, there is a method in which an ethylene-α-olefin copolymer is placed in a sample boat and combusted and decomposed in an Ar / O2 gas flow at a combustion furnace set temperature of 900°C using Thermo Fisher Scientific ICS-1600, and the generated gas is absorbed in an absorption liquid and quantified by ion chromatography.

[0051] In addition, the reduction in the 2,1-insertion of α-olefins makes it possible to further reduce the ethylene chains in the copolymer molecules and suppress the intramolecular crystallinity of ethylene, thereby improving the compatibility with the thermoplastic resin (A) and suppressing the deterioration of mechanical properties and bleed-out. The 2,1-insertion amount of α-olefins can be determined according to the method described in JP-A-7-145212. 13It is determined by analysis of C-NMR measurement, and is preferably less than 1%, further preferably 0 to 0.5%, and further preferably 0 to 0.1%. 13 Particularly preferred is one in which no peak is observed in the range of 15.0 to 17.5 ppm in C-NMR measurement.

[0052] <Other aspects> The α-olefin (co)polymer (B) according to the present invention may be an unmodified product, or may be one to which some polar group has been imparted by graft modification. The vinyl compound having a polar group used for modification may be a vinyl compound having an oxygen-containing group such as acid, acid anhydride, ester, alcohol, epoxy, or ether, a vinyl compound having a nitrogen-containing group such as isocyanate or amide, or a vinyl compound having a silicon-containing group such as vinyl silane.

[0053] Among these, vinyl compounds having an oxygen-containing group are preferred, and specifically, unsaturated epoxy monomers, unsaturated carboxylic acids and their derivatives are preferred. Examples of unsaturated epoxy monomers include unsaturated glycidyl ethers and unsaturated glycidyl esters (e.g., glycidyl methacrylate). Examples of the unsaturated carboxylic acids include acrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, and nadic acid. TM (endo cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid).

[0054] In addition, examples of the derivatives of the unsaturated carboxylic acids include acid halide compounds, amide compounds, imide compounds, acid anhydrides, and ester compounds of the unsaturated carboxylic acids, such as malenyl chloride, maleimide, maleic anhydride, citraconic anhydride, monomethyl maleate, dimethyl maleate, and glycidyl maleate.

[0055] Among these, unsaturated dicarboxylic acids and their acid anhydrides are more preferable, and particularly maleic acid and nadic acid. TMand acid anhydrides thereof are particularly preferably used. The position at which the vinyl compound or its derivative having the polar group is grafted to the α-olefin (co)polymer (B) is not particularly limited, as long as the unsaturated carboxylic acid or its derivative is bonded to any carbon atom of the α-olefin (co)polymer (B).

[0056] When the thermoplastic resin (A) has a polar group, by imparting the polar group to the α-olefin (co)polymer (B), good compatibility between the α-olefin (co)polymer (B) and the thermoplastic resin (A) can be obtained, and deterioration of the mechanical properties of the resin composition and bleeding out can be suppressed.

[0057] The above-mentioned modified product of the α-olefin (co)polymer (B) (modified α-olefin (co)polymer) can be prepared by using various conventionally known methods, for example, the following method. (1) A method in which the above-mentioned α-olefin (co)polymer (B) is mixed in an extruder, a batch reactor, or the like, and a vinyl compound having a polar group or a derivative thereof is added to carry out graft copolymerization. (2) A method in which the above-mentioned α-olefin (co)polymer (B) is dissolved in a solvent, and a vinyl compound having a polar group or a derivative thereof is added to carry out graft copolymerization.

[0058] In any of the above methods, the graft reaction is preferably carried out in the presence of a radical initiator in order to efficiently graft copolymerize the graft monomer of the vinyl compound or derivative thereof having a polar group.

[0059] As the radical initiator, for example, an organic peroxide, an azo compound, etc. are used. As the organic peroxide, benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, etc. are mentioned, and as the azo compound, azobisisobutylnitrile, dimethylazoisobutyrate, etc. are mentioned.

[0060] Specific examples of such radical initiators that are preferably used include dialkyl peroxides such as dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 1,4-bis(tert-butylperoxyisopropyl)benzene.

[0061] These radical initiators are used in an amount of usually 0.001 to 1 part by mass, preferably 0.003 to 0.5 parts by mass, and more preferably 0.05 to 0.3 parts by mass, based on 100 parts by mass of the α-olefin (co)polymer (B).

[0062] The reaction temperature in the graft reaction using the above-mentioned radical initiator or in the graft reaction carried out without using any radical initiator is usually set in the range of 60 to 350°C, preferably 120 to 300°C.

[0063] The graft amount of the vinyl compound having a polar group in the modified α-olefin (co)polymer thus obtained is usually 0.01 to 15 mass%, preferably 0.05 to 10 mass%, when the mass of the modified olefin polymer is taken as 100 mass%.

[0064] <Content of α-olefin (co)polymer (B)> The content of the α-olefin (co)polymer (B) in the entire resin composition of the present invention is 0.01 to 3.8 mass %, preferably 0.2 to 3 mass %, more preferably 0.6 to 3 mass %, and particularly preferably 0.6 to 2 mass %.

[0065] If the content of the α-olefin (co)polymer (B) in the entire resin composition is less than the lower limit, the flowability improving effect of the α-olefin (co)polymer (B) is not fully expressed. On the other hand, if the content of the α-olefin (co)polymer (B) in the entire resin composition exceeds the upper limit, the mechanical strength of the resin composition may decrease or bleed out, which is not preferable. In other words, if the content of the α-olefin (co)polymer (B) is within the above range, there is no bleed out, and a resin composition excellent in mechanical strength and moldability is easily obtained, which is preferable. The above effect is particularly useful for the low MFR thermoplastic resin (A) having excellent mechanical strength, since it can improve moldability while maintaining its characteristic mechanical strength.

[0066] Other Ingredients The resin composition of the present invention may contain additives such as antioxidants, ultraviolet absorbers, stabilizers such as light stabilizers, metal soaps, fillers, flame retardants, antibacterial agents, antifungal agents, and pigments, as necessary. Examples of the stabilizer include antioxidants such as hindered phenol compounds, phosphite compounds, and thioether compounds; ultraviolet absorbers such as benzotriazole compounds and benzophenone compounds; and light stabilizers such as hindered amine compounds.

[0067] Examples of the metal soap include stearates such as magnesium stearate, calcium stearate, barium stearate, and zinc stearate. Examples of the filler include glass fiber, silica fiber, metal fiber (stainless steel, aluminum, titanium, copper, etc.), natural fiber (wood flour, wood fiber, bamboo, bamboo fiber, cotton, cellulose, nanocellulose, wool, straw, hemp, flax, kenaf, kapok, jute, ramie, sisal, henequen, corn, nut shells, wood pulp, rayon, cotton, etc.), carbon black, graphite, activated carbon, graphite, carbon nanotubes, carbon nanofibers, carbon nanohorns, graphene nanoplatelets, nanoporous carbon, carbon fiber, silica, glass beads, silicates (calcium silicate), Examples of such powders include inorganic fillers (iron oxide, titanium oxide, magnesium oxide, alumina, etc.), metal oxides (iron oxide, titanium oxide, magnesium oxide, alumina, etc.), metal carbonates (calcium carbonate, barium carbonate, etc.), sulfates (calcium sulfate, barium sulfate, etc.) and various metal (magnesium, silicon, aluminum, titanium, copper, etc.) powders, mica, glass flakes, pumice powder, pumice balloon, aluminum hydroxide, magnesium hydroxide, basic magnesium carbonate, dolomite, calcium titanate, calcium sulfite, asbestos, montmorillonite, bentonite, molybdenum sulfide, organic fillers (lignin, starch, etc.), and products containing these. In particular, fillers having anisotropy in their structure, such as glass fibers, silica fibers, metal fibers, natural fibers, carbon nanotubes, carbon nanofibers, carbon nanohorns, and carbon fibers, are prone to breakage due to shear during kneading, resulting in a decrease in anisotropy and loss of their characteristics. However, the α-olefin (co)polymer (B) is useful because it reduces shear during kneading due to its flow-improving effect, making it easier to maintain anisotropy.

[0068] Examples of the flame retardant include halogenated diphenyl ethers such as degabromo diphenyl ether and octabromo diphenyl ether, halogenated polycarbonates, and other halogen compounds, inorganic compounds such as antimony trioxide, antimony tetraoxide, antimony pentoxide, sodium pyroantimonate, and aluminum hydroxide, and phosphorus compounds. Compounds such as tetrafluoroethylene can be added as flame retardant assistants to prevent dripping.

[0069] Examples of the antibacterial and antifungal agents include organic compounds such as imidazole compounds, thiazole compounds, nitrile compounds, haloalkyl compounds, and pyridine compounds; and inorganic substances and compounds such as silver, silver-based compounds, zinc-based compounds, copper-based compounds, and titanium-based compounds.

[0070] The pigments may be any pigment that has been conventionally used to color synthetic resins. Specifically, metals such as aluminum, silver, and gold; carbonates such as calcium carbonate and barium carbonate; oxides such as ZnO and TiO2; hydroxides such as Al2O3·nH2O and Fe2O3·nH2O; sulfates such as CaSO4 and BaSO4; nitrates such as Bi(OH)2NO3; chlorides such as PbCl2; chromates such as CaCrO4 and BaCrO4; chromates, manganates, and permanganates such as CoCrO4. phosphates;borates such as Cu(BO)2;uranates such as Na2U2O7·6H2O;nitrites such as K3Co(NO2)6·3H2O;silicates such as SiO2;arsenates and arsenites such as CuAsO3·Cu(OH)2;acetates such as Cu(C2H3O2)2·Cu(OH)2;phosphates such as (NH4)2MnO2(P2O7)2;aluminates, molybdates, zincates, antimonates, tungstates, etc. Inorganic pigments such as fluorides, titanates, iron cyanides, phthalates, CaS, ZnS, CdS, graphite, and carbon black; natural organic pigments such as cochineal lake and madder lake; nitroso pigments such as naphthol green Y and naphthol green B; nitro pigments such as naphthol yellow S and pigment chlorin 2G; azo pigments such as permanent red 4R, hansa yellow, brilliant carmine 68, and scarlet 2R; basic dye lakes such as malacaine green and rhodamine B; acid dye lakes such as acid, green lake, and eosin lake; mordant dye lakes such as alizarin lake and purpurin lake; vat dye pigments such as thio-indigo red B and instanthrene orange; and phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green. The above additives can be used in any proportion and by any method of addition as long as the effects of the present invention are not impaired.

[0071] resin composition The resin composition according to the present invention is characterized in that it contains, as essential components, a thermoplastic resin (A) and an α-olefin (co)polymer (B). In addition, it may contain the above-mentioned other components within the range that does not impair the effects of the invention.

[0072] The composition and molecular weight of the resin composition according to the present invention are not particularly limited as long as they do not impair the present invention, but from the viewpoint of obtaining good moldability and mechanical properties, the proportion of components having a molecular weight of less than 5,000 observed by gel permeation chromatography (GPC) is preferably 0.7 to 4.5% of the total components of the resin composition, more preferably 1.0 to 4.5%, even more preferably 1.2 to 4.5%, and particularly preferably 1.3 to 3.0%. Components having a molecular weight of less than 5,000 improve the moldability of the resin composition, but can cause problems such as a decrease in mechanical properties and bleed-out. If the proportion of components having a molecular weight of less than 5,000 in the resin composition is within the above range, it is preferable because it is easy to obtain the effect of improving moldability while suppressing problems such as a decrease in mechanical properties and bleed-out.

[0073] Method for producing resin composition The resin composition according to the present invention is produced by melt-kneading the thermoplastic resin (A), the α-olefin (co)polymer (B), and optional additives. As a method for melt-kneading, a single-screw extruder, a twin-screw extruder, or the like can be used.

[0074] Regarding the method of adding the α-olefin (co)polymer (B) to the thermoplastic resin (A), various methods can be used within the scope of the invention without impairing the effects of the invention. For example, the method of dry-blending the thermoplastic resin (A) and the α-olefin (co)polymer (B) using a high-speed mixer such as a Henschel mixer or a tumbler, and then melt-kneading the mixture, and the method of melt-kneading the α-olefin (co)polymer (B) by adding it directly from an open part or by inserting it using a side feeder or a liquid feed pump while melt-kneading the thermoplastic resin (A) are mentioned. Among the above methods, the method of dry-blending the thermoplastic resin (A) and the α-olefin (co)polymer (B) and then melt-kneading the mixture is preferred because the flowability improving effect of the α-olefin (co)polymer (B) can be obtained from the initial melting stage of the thermoplastic resin (A).

[0075] The temperature during melt kneading is not particularly limited as long as it is a temperature at which the thermoplastic resin (A) and the like can melt. For example, when the thermoplastic resin (A) is polypropylene, the temperature is usually in the range of 190 to 300°C, and preferably in the range of 200 to 250°C.

[0076] <Production method using a masterbatch containing α-olefin (co)polymer (B)> As a method for producing the resin composition according to the present invention, a method is particularly preferred in which an α-olefin (co)polymer (B) is melt-kneaded with a thermoplastic resin (A) to produce a master batch containing an α-olefin (co)polymer (B), and then the thermoplastic resin (A) is added to the master batch containing the α-olefin (co)polymer (B), and the two are melt-kneaded to produce a resin composition.

[0077] The use of a masterbatch containing an α-olefin (co)polymer (B) is preferred because it can prevent a decrease in moldability due to the α-olefin (co)polymer (B) causing slippage in the extruder. In addition, the α-olefin (co)polymer (B) has the property of easily becoming liquid at room temperature even when melt-kneaded with the thermoplastic resin (A), so it softens and melts the components of the thermoplastic resin (A) early in the initial stage of melt-kneading. Therefore, even when the masterbatch containing an α-olefin (co)polymer (B) is kneaded together with the thermoplastic resin (A) in an extruder, it can show a good flowability improving effect.

[0078] The resin composition produced by the production method using the above-mentioned α-olefin (co)polymer (B)-containing masterbatch contains 25 to 99.99 mass% of the thermoplastic resin (A) used in the production of the masterbatch and the thermoplastic resin (A) further added to the masterbatch after the production of the masterbatch, and 0.01 to 3.8 mass% of the α-olefin (co)polymer (B).

[0079] The thermoplastic resin (A) used in the production of the masterbatch containing the α-olefin (co)polymer (B) and the thermoplastic resin (A) further added to the masterbatch after the production of the masterbatch may be the same resin or different resins.

[0080] The method for producing the masterbatch containing the α-olefin (co)polymer (B) is not particularly limited, and examples thereof include a method of melt-kneading the α-olefin (co)polymer (B) and the thermoplastic resin (A) and, if necessary, additives, using a single-screw extruder, a twin-screw extruder, a plastomill, a Brabender, a kneader, a roll mixer, a Banbury mixer, etc. Among these, a method using a single-screw extruder or a twin-screw extruder is preferred from the viewpoints of ease of mass production and ease of obtaining a pellet-shaped masterbatch, and a method using a twin-screw extruder is particularly preferred from the viewpoints of increasing the compatibility of the α-olefin (co)polymer (B) and suppressing bleed-out.

[0081] The temperature during melt kneading in the production of the masterbatch is not particularly limited as long as it is a temperature at which the thermoplastic resin (A) and the like can melt. For example, when the thermoplastic resin (A) is polypropylene, the temperature is usually in the range of 190 to 300°C, and preferably in the range of 200 to 250°C.

[0082] The amount of the α-olefin (co)polymer (B) in the α-olefin (co)polymer (B)-containing masterbatch used in the present invention is not particularly limited, but is usually in the range of 0.1 to 100 parts by mass, preferably in the range of 0.1 to 20 parts by mass, more preferably in the range of 0.5 to 10 parts by mass, and particularly preferably in the range of 3 to 10 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A) contained in the α-olefin (co)polymer (B)-containing masterbatch.

[0083] When the α-olefin (co)polymer (B) is blended at a mass equal to or greater than the lower limit of the above range, the α-olefin (co)polymer (B) makes it easier for the thermoplastic resin (A) to soften and melt, and when the α-olefin (co)polymer (B)-containing masterbatch and the thermoplastic resin (A) are melt-kneaded in an extruder, a good flowability improvement effect is obtained, which is preferable. Also, when the α-olefin (co)polymer (B) is blended at a mass equal to or less than the upper limit of the above range, the bleed-out of the α-olefin (co)polymer (B) can be suppressed, and a non-sticky α-olefin (co)polymer (B)-containing masterbatch can be obtained, which is preferable.

[0084] The method for melt-kneading the masterbatch containing the α-olefin (co)polymer (B) with the thermoplastic resin (A) added to the masterbatch is not particularly limited, and for example, the same melt-kneading method as in the above-mentioned method for producing the masterbatch containing the α-olefin (co)polymer (B) can be used.

[0085] The ratio of the amount of the master batch containing the α-olefin (co)polymer (B) to the amount of the thermoplastic resin (A) added to the master batch is preferably 1 to 110 parts by mass of the master batch containing the α-olefin (co)polymer (B), more preferably 15 to 110 parts by mass, and particularly preferably 15 to 50 parts by mass, per 100 parts by mass of the thermoplastic resin (A) added to the master batch. If the ratio of the amount of the master batch containing the α-olefin (co)polymer (B) to the amount of the thermoplastic resin (A) added to the master batch is smaller than the lower limit of the above range, the content of the α-olefin (co)polymer (B) in the resin composition is reduced, and the effect of improving moldability may be difficult to be achieved. On the other hand, if the ratio of the amount of the master batch containing the α-olefin (co)polymer (B) to the amount of the thermoplastic resin (A) added to the master batch is greater than the upper limit of the above range, the content of the α-olefin (co)polymer (B) is increased, which is likely to cause a decrease in mechanical properties.

[0086] Molded body The molded article of the present invention is a molded article containing the above-mentioned resin composition. The molded article of the present invention can be obtained, for example, by melt-kneading the above-mentioned thermoplastic resin (A) and α-olefin (co)polymer (B). In this case, as described above, a master batch containing α-olefin (co)polymer (B) may be produced, and the thermoplastic resin (A) may be further added to the master batch and melt-kneaded. In addition, the above-mentioned resin composition may be melt-kneaded and then immediately molded to obtain a molded article.

[0087] Examples of the molding method include T-die molding, blow molding, injection molding, and other known molding methods. For example, when polypropylene is used as the thermoplastic resin (A) and an extruded sheet or film is formed by T-die extrusion or the like, a molded product is obtained by extrusion molding usually in the range of 170 to 300° C., preferably 180 to 270° C., and more preferably 190 to 250° C. A stretched film is obtained by stretching a film extruded from an extruder, for example, by a tenter method (longitudinal and transverse stretching, transverse and longitudinal stretching), a simultaneous biaxial stretching method, or a uniaxial stretching method.

[0088] When the molded article of the present invention is obtained by extrusion blow molding using polypropylene as the thermoplastic resin (A), the resin is extruded from a die as a tubular parison at a resin temperature in the range of 170 to 240° C., and then the parison is held in a mold having a desired shape, and air is blown into the mold, and the molded article is obtained at a resin temperature in the range of 160 to 230° C. In addition, the molded article may be stretched to an appropriate ratio during extrusion blow molding.

[0089] When injection molding is performed using polypropylene as the thermoplastic resin (A), the cylinder temperature during injection molding is usually in the range of 180 to 400°C, preferably 200 to 300°C, and more preferably 200 to 250°C, the injection pressure is usually in the range of 10 to 200 MPa, and preferably 20 to 150 MPa, and the mold temperature is usually in the range of 20 to 200°C, preferably 20 to 80°C, and more preferably 20 to 60°C. EXAMPLES

[0090] The present invention will be described below with reference to examples, but the present invention is not limited to these examples in any way. In the following examples and comparative examples, the physical properties were measured or evaluated by the following methods.

[0091] [Methyl group indicator] The nuclear magnetic resonance spectrometer, EX270 manufactured by JEOL Ltd., was used. The solvent was deuterated chloroform, the sample concentration was 55 mg / 0.6 mL, the measurement temperature was room temperature, and the observation nuclei were 1 The measurements were performed using H (270 MHz), a single pulse sequence, a pulse width of 6.5 μs (45° pulse), a repetition time of 5.5 s, an accumulation count of 16, and a chemical shift reference value of 7.24 ppm of the solvent peak based on CHCl3 in deuterated chloroform.

[0092] Measured as above 1The ratio of the integral value of the peak in the range of 0.50 to 1.15 ppm to the integral value of the peak in the range of 0.50 to 2.20 ppm in the spectrum obtained from the H-NMR spectrum was taken as the methyl group index. Here, the peaks due to α-olefin (co)polymers are almost included in the range of 0.50 to 2.20 ppm. Of this range, the peaks due to methyl groups are likely to be included in the range of 0.50 to 1.15 ppm.

[0093] [Melting Point] The melting point was measured using a Seiko Instruments X-DSC-7000. Approximately 8 mg of the sample was placed in a simple, airtight aluminum sample pan and placed in a DSC cell. The DSC cell was heated from room temperature to 150°C at 10°C / min under a nitrogen atmosphere, then held at 150°C for 5 minutes, then cooled at 10°C / min, and the DSC cell was cooled to -100°C (cooling down process). Next, the sample was held at -100°C for 5 minutes, then heated to 150°C at 10°C / min, and the temperature at which the enthalpy curve obtained during the heating process showed a maximum was taken as the melting point (Tm), and the sum of the endothermic heat associated with melting was taken as the heat of fusion (ΔH). If no peak was observed or the value of the heat of fusion (ΔH) was 1 J / g or less, the melting point (Tm) was considered not to be observed. The melting point (Tm) and heat of fusion (ΔH) were determined according to JIS K7121.

[0094] [Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)] The molecular weight of the α-olefin (co)polymer (B) was measured using the following high-speed GPC measuring device. Calibration was performed using monodisperse polystyrene with a known molecular weight as a standard substance. Measuring device: Tosoh HLC8320GPC Mobile phase: THF (Wako Pure Chemical Industries, Ltd., stabilizer-free, liquid chromatography grade) Column: Two TSKgel Super MultiporeHZ-M columns manufactured by Tosoh Corporation were connected in series. Sample concentration: 5mg / mL Mobile phase flow rate: 0.35mL / min Measurement temperature: 40℃ Standard sample for calibration curve: Tosoh PStQuick MP-M The molecular weight of the polyethylene wax used in the Comparative Examples was measured using the following measuring device. Calibration was performed using monodisperse polystyrene with a known molecular weight as a standard substance. Measuring device: Tosoh HLC-8321GPC / HT model Mobile phase: o-dichlorobenzene Column: Two TSKgel GMH6-HT columns and two TSKgel GMH6-HTL columns connected in series (Tosoh Corporation) Sample concentration: 0.1mg / mL Mobile phase flow rate: 1.0mL / min Measurement temperature: 140℃ Standard sample for calibration curve: Tosoh monodisperse polystyrene #3 std set

[0095] 〔density〕 The density of the thermoplastic resin (A) and the polyethylene wax used in the comparative examples was determined by the density gradient tube method in accordance with JIS K7112. The density of the α-olefin (co)polymer (B) was determined by the pycnometer method in accordance with JIS K2249-3.

[0096] [MFR] The MFR of the thermoplastic resin (A) was measured in accordance with JIS K 7210 under conditions of 230° C. and a test load of 2.16 kgf. In the following Examples and Comparative Examples, the following raw materials were used.

[0097] Thermoplastic resin (A) [Production Example of Thermoplastic Resin (A)] A 10-liter continuous polymerization reactor, fully purged with nitrogen, was filled with 6000 ml of dehydrated and purified hexane, and 100 mmol of triethylaluminum and 10 mmol of a solid titanium catalyst component prepared according to the method of Example 1 of JP-A-58-38006 were charged in terms of titanium atoms. Then, propylene was continuously fed into the reactor for 1 hour so that the total amount was 50 g per 10 g of titanium component. The temperature was kept at 10°C during this period. After 1 hour, the introduction of propylene was stopped and the reactor was fully purged with nitrogen. The solid part of the obtained slurry was washed five times with purified hexane to obtain titanium-containing polypropylene. Next, a 2000-liter continuous polymerization reactor, fully purged with nitrogen, was charged with 500 kg of propylene, 0.173 mol of cyclohexylmethyldimethoxysilane, and 10 L of hydrogen, and the internal temperature of the polymerization reactor was raised to 65°C. Next, the titanium-containing polypropylene obtained above was charged at 0.00650 mol in terms of titanium atoms, and the internal temperature of the polymerization vessel was raised to 70°C, and propylene polymerization was carried out for 1 hour. After 1 hour, the introduction of propylene was stopped, and the reactor was thoroughly substituted with nitrogen to obtain a white granular polymer. The obtained polymer was dried under reduced pressure at 70°C, and then extruded at 230°C using an extrusion granulator with a screw diameter of 65 mm, and pelletized to obtain polypropylene, which is thermoplastic resin (A). The obtained polypropylene was designated as thermoplastic resin (a). The obtained thermoplastic resin (a) had a weight average molecular weight (Mw): 609,000, MFR: 3.0 g / 10 min, and density: 910 kg / m 3 It was.

[0098] α-Olefin (co)polymer (B) [Production Example of α-Olefin (Co)polymer (B)] A 2-liter continuous polymerization reactor equipped with an agitator and fully purged with nitrogen was filled with 1 liter of dehydrated and purified hexane, and ethylaluminum sesquichloride (Al(C2H5) 1.5 ·Cl 1.5) in hexane at a rate of 500ml / h for 1 hour, and then a hexane solution of VO(OC2H5)Cl2 adjusted to 16mmol / L as a catalyst at a rate of 500ml / h and hexane at a rate of 500ml / h were continuously fed. Meanwhile, the polymerization liquid was continuously extracted from the top of the polymerization vessel so that the polymerization liquid in the polymerization vessel was always 1 liter. Next, ethylene gas was fed at a rate of 35L / h, propylene gas at a rate of 35L / h, and hydrogen gas at a rate of 80L / h using a bubbling tube. The copolymerization reaction was carried out at 35°C by circulating a coolant through a jacket attached to the outside of the polymerization vessel. As a result, a polymerization solution containing an ethylene-propylene copolymer was obtained. The obtained polymerization solution was deashed with hydrochloric acid, poured into a large amount of methanol to precipitate the ethylene-propylene copolymer, and then dried under reduced pressure at 130°C for 24 hours to obtain an α-olefin (co)polymer (B). The obtained α-olefin (co)polymer was named α-olefin (co)polymer (b). The obtained α-olefin (co)polymer (b) had a methyl group index of 47.6%, a weight average molecular weight (Mw): 4170, a molecular weight distribution (Mw / Mn): 1.7, and a density of 843 kg / m 3 and no melting point was observed.

[0099] Polyethylene wax [Production Example of Polyethylene Wax] 1. Catalyst Preparation In a glass autoclave with an internal volume of 1.5 liters, 25 g of commercially available anhydrous magnesium chloride was suspended in 500 ml of hexane. This was kept at 30°C and stirred while 92 ml of ethanol was added dropwise over 1 hour, and the reaction was continued for another 1 hour. After the reaction was completed, 93 ml of diethylaluminum monochloride was added dropwise over 1 hour, and the reaction was continued for another 1 hour. After the reaction was completed, 90 ml of titanium tetrachloride was added dropwise, and the reaction vessel was heated to 80°C and the reaction was continued for 1 hour. After the reaction was completed, the solid portion was washed with hexane by decantation until no free titanium was detected. This was suspended in hexane and the titanium concentration was quantified by titration, and the suspension was used for the following experiment.

[0100] 2.Production of polyethylene wax 930 ml of hexane and 70 ml of propylene were charged into a 2-liter stainless steel autoclave that had been thoroughly purged with nitrogen, and hydrogen was introduced until the pressure reached 0.1 MPa (gauge pressure). Next, the temperature inside the system was raised to 170°C, and 0.1 mmol of triethylaluminum, 0.4 mmol of ethylaluminum sesquichloride, and the hexane suspension of the solid obtained above were injected with ethylene so that the amount of titanium component was 0.008 mmol in atomic terms to initiate polymerization. Then, ethylene alone was continuously fed to maintain the total pressure at 2.9 MPa (gauge pressure), and polymerization was carried out at 170°C for 40 minutes.

[0101] After the polymerization was terminated by adding a small amount of ethanol to the system, the unreacted ethylene and propylene were purged. The resulting polymer solution was dried overnight at 100°C under reduced pressure to obtain a polyethylene wax. The resulting polyethylene wax had a density of 926 kg / m 3 , weight average molecular weight (Mw): 10,270, molecular weight distribution (Mw / Mn): 2.8, melting point: 109°C.

[0102] Example 1 [Preparation of Masterbatch (1)] In a 15 mmφ twin-screw extruder, thermoplastic resin (a) was added from the hopper and α-olefin (co)polymer (b) was added from the C5 vent in the ratios shown in Table 1. The mixture was melt-kneaded and then formed into pellets using a pelletizer to produce master batch (1).

[0103] [T-die film molding] A 20 mmφ single-screw extruder (Toyo Seiki Seisakusho Co., Ltd., D2020) was equipped with a T-die with a die width of 150 mm, and the rotation speed was set to 25 rpm, the cylinder temperature, and the die temperature to 205°C. The resin composition obtained by dry blending the thermoplastic resin (a) and the master batch (1) in the composition shown in Table 2 was added from a hopper to perform extrusion film molding to obtain a film with a thickness of 50 μm.

[0104] Example 2 A film was obtained in the same manner as in Example 1, except that the blending ratio of the thermoplastic resin (a) and the master batch (1) during T-die film molding was set to the ratio shown in Table 2.

[0105] Example 3 [Production of master batch (2)] A master batch (2) was obtained in the same manner as in Example 1, except that the blending ratio of the thermoplastic resin (a) and the α-olefin (co)polymer (b) was set to the ratio shown in Table 1.

[0106] [T-die film molding] A film was obtained in the same manner as in Example 1, except that the master batch (2) was used instead of the master batch (1) and the blending ratio of the thermoplastic resin (a) and the master batch (2) during T-die film molding was set to the ratio shown in Table 2.

[0107] Comparative Example 1 A film was obtained in the same manner as in Example 1, except that in the T-die film molding, no master batch was used and only the thermoplastic resin (a) was used.

[0108] Comparative Example 2 A film was obtained in the same manner as in Example 3, except that the blending ratio of the thermoplastic resin (a) and the master batch (2) during T-die film molding was set to the ratio shown in Table 2.

[0109] Comparative Example 3 A film was obtained in the same manner as in Example 1, except that the above polyethylene wax was used instead of the master batch (1) and the blending ratio of the thermoplastic resin (a) and the polyethylene wax during T-die film molding was set to the ratio shown in Table 2.

[0110] Comparative Example 4 A film was obtained in the same manner as in Comparative Example 3, except that the blending ratio of the thermoplastic resin (a) and the polyethylene wax during T-die film molding was set to the ratio shown in Table 2. The moldability during T-die film molding and the physical properties of the obtained film were evaluated for the following items. The results are shown in Table 2.

[0111] [Extrusion torque] The resin was charged from the hopper, and the extruder was set to the above molding conditions. The torque value indicated by the extruder was measured for 1 minute starting 10 minutes later, and the average value was calculated. If this value is small, it is difficult to reach the upper limit of the device's capacity even when the extrusion torque increases during molding, making it easier to reduce unevenness in the discharge volume during molding. Also, if this value is small, it is difficult to reach the upper limit of the device's capacity when the screw rotation speed of the extruder is increased, making it easier to adjust the discharge volume.

[0112] [Discharge amount] The resin was charged from the hopper, and the extruder was set under the above molding conditions. 10 minutes later, the mass of the film extruded per minute was measured, and the extrusion rate per hour was calculated from this value.

[0113] [Tensile breaking strength · Tensile breaking elongation · Tensile tensile product] According to JIS K7127, measurements were taken in the machine direction of the film to determine the strength and elongation at which the film broke, which were taken as the tensile breaking strength and tensile breaking elongation, respectively. The product of the tensile breaking strength and tensile breaking elongation was taken as the tensile tensile product. The larger this value, the more difficult the film is to break, and a value of 30,000 MPa·% or more in particular indicates that the film is resistant to breakage.

[0114] [Ratio of components with molecular weight less than 5,000] The molecular weights of the components contained in the obtained film were measured using the following measuring device, and the proportion of components with a molecular weight of less than 5,000 was calculated from the ratio of the peak area of ​​components with a molecular weight of less than 5,000 to the total peak area. Calibration was performed using monodisperse polystyrene of known molecular weight as a standard substance. Measuring device: Tosoh HLC-8321GPC / HT model Mobile phase: o-dichlorobenzene Column: Two TSKgel GMH6-HT columns and two TSKgel GMH6-HTL columns connected in series (Tosoh Corporation) Sample concentration: 0.1mg / mL Mobile phase flow rate: 1.0mL / min Measurement temperature: 140℃ Standard sample for calibration curve: Tosoh monodisperse polystyrene #3 std set

[0115] [Table 1]

[0116] [Table 2]

[0117] From the results in Table 2, it can be seen that in Examples 1 to 3, the extrusion torque is smaller and the discharge amount is larger than in Comparative Example 1. This shows that, compared to Comparative Example 1 in which the thermoplastic resin (a) was molded alone, in Examples 1 to 3 in which the α-olefin (co)polymer (b) was added to the thermoplastic resin (a) and molded, the moldability was improved.

[0118] In addition, it can be seen that, in Examples 1 to 3, the decrease in tensile breaking strength is slight, but the tensile breaking elongation is greatly improved, compared to Comparative Example 1. This is believed to be because the α-olefin (co)polymer (b) exhibits good compatibility with the amorphous portion of the thermoplastic resin (a). As a result, in Examples 1 to 3, the tensile product is improved, and molded articles that are more resistant to breakage are obtained.

[0119] On the other hand, when Examples 1 to 3 are compared with Comparative Example 2, it is found that, although the improvement effect on moldability is low in Examples 1 to 3, the tensile product value is large and a film resistant to breakage is obtained. This is considered to be because, in Comparative Example 2, the amount of α-olefin (co)polymer (b) added is large, so that the tensile breaking strength is significantly reduced, whereas, in Examples 1 to 3, the amount of α-olefin (co)polymer (b) added is kept within an appropriate range, so that the reduction in the tensile breaking strength can be suppressed.

[0120] From the results in Table 2, when Examples 1 to 3 and Comparative Examples 3 to 4 are compared with Comparative Example 1, it can be seen that in Comparative Examples 3 to 4, the extrusion torque is significantly decreased compared to Comparative Example 1, but the discharge amount is also significantly decreased. This indicates that slippage occurs in the extruder due to the molding aid, and moldability is reduced. In contrast, in Examples 1 to 3, the α-olefin (co)polymer (b) and the thermoplastic resin (a) are added as a master batch in which they are melt-kneaded in advance, so that the occurrence of slippage can be prevented, and the effects of reducing the extrusion torque and increasing the discharge amount are obtained, and good moldability is obtained. In addition, when Examples 1 to 3 are compared with Comparative Examples 3 to 4, Examples 1 to 3 show large values ​​for tensile breaking strength, tensile breaking elongation, and tensile product, indicating that the molded product is resistant to breakage. This is considered to be because the α-olefin (co)polymer (b) has better compatibility than polyethylene wax. The α-olefin (co)polymer (b) is characterized by not only improving moldability but also enabling the production of a molded product that is difficult to break.

Claims

1. A resin composition comprising 90 to 99.99 mass% of a thermoplastic resin (A) having a polystyrene-equivalent weight average molecular weight (Mw) of 5,000 or more as measured by gel permeation chromatography (GPC), and 0.01 to 3.8 mass% of an α-olefin (co)polymer (B) satisfying the following requirements (b-1) to (b-4): The thermoplastic resin (A) is a polyolefin, The resin composition, wherein the α-olefin (co)polymer (B) is a copolymer of ethylene and an α-olefin having 3 or more carbon atoms. (b-1) 1 The methyl group index measured by H-NMR is 25 to 60%. (Here, the methyl group index is determined by dissolving the α-olefin (co)polymer in deuterated chloroform.) 1 H-NMR was measured, and CHCl 3 (The ratio of the integral value of the peak within the range of 0.50 to 1.15 ppm to the integral value of the peak within the range of 0.50 to 2.20 ppm, when the solvent peak appearing at 7.24 ppm based on the above is used as a reference.) (b-2) No melting point is observed in differential scanning calorimetry (DSC). (b-3) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is from 1,000 to 20,000. (b-4) Density measured by pycnometer method is 810 to 870 kg / m 3 It is.

2. 2. The resin composition according to claim 1, wherein the thermoplastic resin (A) is polypropylene.

3. A resin composition according to claim 1 or 2, wherein the α-olefin (co)polymer (B) is an ethylene-propylene copolymer.

4. The resin composition according to any one of claims 1 to 3, wherein the proportion of components having a molecular weight of less than 5,000 as determined by gel permeation chromatography (GPC) is in the range of 0.7 to 4.5 mass% based on the total components.

5. The method for producing the resin composition according to any one of claims 1 to 4, comprising the steps of: kneading 0.1 to 100 parts by mass of the α-olefin (co)polymer (B) with 100 parts by mass of the thermoplastic resin (A) to obtain a master batch; and kneading the thermoplastic resin (A) and the master batch in an extruder.

6. A molded article comprising the resin composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Production of photomask having phase shift layer

    JP1993080492A

  • Polyacetal resin composition

    JP1998330582A

  • Polyolefin resin composition and polyolefin film obtained therefrom

    JP2001294717A

  • Applications of polyolefin waxes in the field of synthetic resin processing

    JP2003528948A

  • Polyamide resin composition

    JP2018104530A